Effect of the pandemic-induced shift to teleworking on worker-level wage and hours worked - Floro, Nicarae Valerie M.; Panagsagan, Ruth A.; Jandoc, Karl Robert (Quezon City School of Economics, University of the Philippines Diliman, 2022)
This study examines the effect of the pandemic-induced shift to teleworking on worker-level wage and hours worked in the Philippines. Data from the October 2019 round and October 2020 round of the Philippine Labor Force Survey (LFS) were used in order to compare pre-pandemic to pandemic figures. Specifically, this study aims to look at the relationship between an occupation’s teleworkability score and the change in its workers’ wages and hours worked by performing an Ordinary Least Squares regression analysis. This paper finds that higher teleworkability of an occupation is associated with lower wages and greater weekly work hours during the pandemic. The reduction in wages may be explained by lower productivity, flexible time arrangements and initial costs of implementing ICTs for telework which vary across countries. Meanwhile, the increase in weekly work hours implies the blurring of work-life boundaries and difficulty in adjusting to new technological tools among workers in high teleworkable occupations.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bilbliographical references and appendices.
Keywords: COVID-19 Pandemic -- 2020-2023.; Telework -- COVID-19 Pandemic